THE ROLE OF DYSLIPIDEMIA IN THE PATHOGENESIS OF DIABETIC ANGIOPATHIES AND ITS CORRECTION BY CRATAEGUS PENTAGYNA - Badalova, A.T.; Aliyeva, A.J.; Aliyev, S.H.; Huseynova, Sh.M.; Aliyeva, J.T.; Hajiyeva, S.I.; Jafarova, N.A. (World of Medicine and Biology, 2025)
Diabetes mellitus is one of the important medical and social problems facing the healthcare systems of all countries of the world. Dyslipidemia plays a significant role in the pathogenesis of vascular complications of the disease. In this regard, correction of blood lipid composition is inevitable. To contribute to the solution of the problem, we conducted an experimental study on 21 rabbits. Blood lipid parameters were studied against the background of the combined effect of atorvastatin and hawthorn during experimental diabetes. It was found that when atorvastatin is used together with phytotherapy, the amount of atherogenic lipoproteins decreases sharply, and the level of anti-atherogenic lipoproteins increases. It can be concluded that it is recommended to add phytotherapy with statins to the dyslipidemia correction protocol.